The Role of Public Relations in College Athletics: Identifying Roles, Tasks, and Importance of Public Relations - Brody J. Ruihley; Angela N. Pratt; Tiffany Carpenter (Journal of Applied Sports Management, 2016)
Public relations (PR) is becoming increasingly important in college athletics as the frequency and severity of controversy, legal issues, and crises heighten. With many stakeholders concerned about college athletic programs, coupled with an increased media presence and skyrocketing budgets, it is imperative that athletic programs communicate effectively and efficiently in times where clarity is needed. With that, the purpose of this research is to continue learning about the roles and perceptions of PR within an athletic department, as seen through the lens of ath-letic directors. Building on the work of (Ruihley & Fall, 2009), this research seeks to discover more about the following PR areas: tasks, stakeholder reach, benefits, and roles of PR staff. With mixed-method findings from NCAA Divisions I-A and I-AA athletic directors ( n = 49), results indicate top responsibilities of the pri-mary PR staff member as maintaining media contacts and working with coaches and athletes. The top stakeholders indicated were student athletes, media, and the university. The top perceived role was problem-solving process facilitator. Lastly, the top indicated benefits of PR were identified in themes of communication and message, relationships, and strategic planning. The results of this research assist in understanding more about the fit of PR in college athletics.
Keywords: public relations; roles; athletic director; college athletics; PR in college athletics